Use of Misoprostol in the Management of Early Pregnancy Loss - Gurung, G; Rana, A; Baral, J (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: To evaluate the effectiveness of Misoprostol administered vaginally to assist complete evacuation in early pregnancy losses (incomplete abortion, missed abortion and blighted ovum). Methods: It is a descriptive study conducted in the Department of Ob/Gyn and Emergency Department Tribhuvan University Teaching hospital. All women with clinical/USG diagnosis of incomplete abortion, missed abortion and blighted ovum ≤12 weeks POG either from last menstrual period (LMP) or USG were inserted tab. misoprostol 800 mcg in the posterior fornix. Same dose was repeated when the evacuation was incomplete on day 3 of follow-up. Manual vacuum aspiration (MVA) was offered on day 14 if evacuation was incomplete or any complications like excessive bleeding/severe pain occurred during this period. Results: A hundred and thirty three women with incomplete/missed/blighted ovum were reported, of which 112 (84.3%) were analyzed as 21(15.7%) lost to follow up. Among the 112, 51 (45.5%) were incomplete abortion, 34(30.3%) blighted and 27 (24.1%) missed abortion. Complete evacuation was achieved in 98/112 (87.5%) cases [73 (65%) cases with single dose & 25(22.3%) with double doses]. Evacuation was failed in 14(12.5%) cases [incomplete abortion 6 (42%), blighted 7 (50%) & missed abortion 1 (7.1%)]. Failure for complete evacuation (n=14) related to gestational age: 10-12 weeks 9/14(64%), 7-9 weeks 5 (35%) and none in the ≤6 weeks. Although the plan was to evacuate on day 14 of follow-up for incomplete evacuation which was applicable only in 11(78.5%) cases, 3(21.5%) cases were surgically (MVA) treated beforehand (2 for excessive bleeding, 1 for severe pain). No severe complications and side effects requiring treatment were observed. Conclusions: Vaginal Misoprostol is proved to be effective and safe in cases of incomplete abortion, missed abortion and blighted ovum. In the cases that failed to achieve complete evacuation by medical means using misoprostol were subjected to surgical manual vacuum aspiration (MVA) on day 14 of follow-up. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11133 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 9-13